2006
DOI: 10.1021/cm0524446
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Polymerization of Carbon Monoxide:  Disproportionation and Synthesis of an Energetic Lactonic Polymer

Abstract: We have studied pressure-induced chemical reactions in carbon monoxide using both a diamond-anvil cell and a modified large volume press. Our spectroscopic data reveal that carbon monoxide disproportionates into molecular CO 2 and a solid lactone-type polymer; photochemically above 3.2 GPa, thermochemically above 5 GPa at 300K, or at 3 GPa and ~2000K as achieved by laser heating. The solid product can be recovered at ambient conditions with a high degree of conversion, measured to be up to 95% of the original … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

14
116
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(131 citation statements)
references
References 40 publications
14
116
1
Order By: Relevance
“…Layered structures also appear in the polymerized solids of other molecules, such as N 2 [31] and CO 2 [26]. Structures with conjugated C ¼ C bonds as suggested by experiments [10,11] also appear in our search, but they are higher in energy than the chainlike polymers and purely single-bonded structures.…”
mentioning
confidence: 57%
See 3 more Smart Citations
“…Layered structures also appear in the polymerized solids of other molecules, such as N 2 [31] and CO 2 [26]. Structures with conjugated C ¼ C bonds as suggested by experiments [10,11] also appear in our search, but they are higher in energy than the chainlike polymers and purely single-bonded structures.…”
mentioning
confidence: 57%
“…Pressure-induced polymerization of molecular crystals results in materials with entirely new electronic, optical, and physical properties [1,2]. CO is one of the most extensively studied molecular crystals [3][4][5][6][7][8][9][10][11][12]. Studies of polymerization of CO are motivated by the desire to understand the fundamental physics and chemistry of geological and planetary processes, where CO is present, and to search for new materials [13] exhibiting properties such as ''high energy density'' [10] and ''superhardness'' [14,15].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Yamanaka et al [3] reported a martensitic structural phase transition in CaFe 2 O 4 at~50 GPa accompanied by a large volume drop. However, Merlini et al [4] based on single-crystal XRD claimed no change in symmetry, suggesting, based on the disappearance of the K â' satellite peak observed by XES, that the volume drop is a result of a high-spin (HS) to low-spin (LS) transition.…”
mentioning
confidence: 99%